Resin composite material and method for producing the same, and molded article

JP2025030746APending Publication Date: 2025-03-07SHIMADA SHOKAI CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023136307
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-24
Publication Date
2025-03-07

AI Technical Summary

Benefits of technology

【0010】 本発明により、水分を多く含む廃棄物を原材料に用いることができ、合成樹脂の連続相にセルロース系バイオマスの分散相を均一かつ微細に形成した樹脂複合材料の製造技術が提供される。これにより、リサイクル回収物の樹脂複合材料への活用を促進し、合成樹脂の使用量を削減し、持続可能な開発目標(SDGs)の実現に大きく貢献することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025030746000001_ABST
    Figure 2025030746000001_ABST
Patent Text Reader

Abstract

To provide a technique for producing a resin composite material that makes a waste containing much moisture usable in a raw material, in which a dispersion phase of cellulose-based biomass is uniformly and finely formed in a continuous phase of a synthetic resin.SOLUTION: A resin composite material includes: a solvent container 28 for storing a solvent 18; a solute container 29 for storing a solute 19 to be dissolved in the solvent 18; a dissolution tank 26 which dissolves the solute 19 in the solvent 18, and converts it into a paste-like body 16; a filler container 27 for storing a cellulose-based filler 17; a first mixing tank 21 for mixing the paste-like body 16 with the cellulose-based filler 17, and converting it into a premix body 11; a resin container 25 for storing a pellet-like synthetic resin 15; and a second mixing tank 22 for mixing the premix body 11 with the synthetic resin 15, and converting it into a mixed body 12.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a production technology for resin composite materials that utilize cellulose resources, which contributes to the realization of the Sustainable Development Goals (SDGs). [Background technology]

[0002] By dispersing and compounding biomass and underutilized waste resources as fillers in synthetic resins, the amount of synthetic resins produced from fossil resources used can be reduced, and resin composite materials that contribute to the realization of the SDGs are being developed.

[0003] In the case of molded products made from resin composite materials, there are regulations that allow them to be labeled as non-plastic products if the synthetic resin content is less than 50%. There are also regulations that allow them to be labeled as paper products if the paper content is 50% or more. Furthermore, there are studies underway to widely use waste materials as raw materials for manufacturing resin composite materials that meet these regulations.

[0004] Meanwhile, a technology for producing a resin composite material has been disclosed that can form a thin film from waste with a high moisture content without drying treatment by adding a moisture-absorbing substance (for example, Patent Document 1). This invention includes a process in which a water-containing filler and a water-absorbing filler are mixed in advance, and the water contained in the water-containing filler is absorbed by the water-absorbing filler to form a mixture. Then, by heating and kneading this mixture with a synthetic resin, a resin composite material is produced in which a dispersed phase of the filler that is hydrogen-bonded to water is uniformly and finely formed in the continuous phase of the synthetic resin. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 7061239 Summary of the Invention [Problem to be solved by the invention]

[0006] Cellulosic biomass is a resource produced by fixing carbon dioxide from the atmosphere. For this reason, it can be said that manufacturing technology for resin composite materials using cellulosic biomass will greatly contribute to the realization of the Sustainable Development Goals (SDGs). However, it has been difficult to manufacture resin composite materials in which a dispersed phase of cellulosic biomass is uniformly and finely formed in a continuous phase of synthetic resin.

[0007] In addition, the recovery of large amounts of discarded stretch film used for packaging and other purposes and its reuse as synthetic resins that make up resin composite materials are being considered. Incidentally, the recycling of stretch film involves washing, drying, and crushing the recovered material, which is then fed into an extruder and repelletized. However, this crushed material has a high bulk density and is prone to scattering, making the recycling of stretch film inefficient. To improve the efficiency of recycling, it would be advantageous if the crushed material from the recovered stretch film could be mixed with cellulosic biomass while it still retains moisture without being dried.

[0008] The present invention has been made in consideration of the above circumstances, and aims to provide a production technology for a resin composite material in which waste materials containing a large amount of moisture can be used as raw materials and a dispersed phase of cellulosic biomass is uniformly and finely formed in a continuous phase of synthetic resin. [Means for solving the problem]

[0009] The method for producing a resin composite material according to the present invention includes the steps of preparing a paste-like body in which at least one of polysaccharide nanofibers and a hydrophilic cellulose derivative is used as a solute and dissolved in a solvent; preparing a cellulose-based filler having a powder, fibrous or cotton-like shape and an average width of 20 to 60 μm; pouring a mixture of at least the paste-like body, the cellulose-based filler and a synthetic resin into a sealed container; heating and kneading the mixture at a temperature at which the synthetic resin melts to form a molten kneaded body; and opening the sealed container to discharge the vaporized solvent to the outside and then removing the molten kneaded body. Effect of the Invention

[0010] The present invention provides a technology for producing resin composite materials that can use waste materials containing a large amount of moisture as raw materials and that have a uniform and finely dispersed cellulosic biomass phase in a continuous phase of synthetic resin. This will promote the use of recycled materials in resin composite materials, reduce the amount of synthetic resin used, and greatly contribute to the realization of the Sustainable Development Goals (SDGs). [Brief description of the drawings]

[0011] [Figure 1] 1 is a side view showing an example of a production system for carrying out a method for producing a resin composite material according to a first embodiment of the present invention. [Diagram 2] FIG. 4 is a side view showing an example of a production system for carrying out a method for producing a resin composite material according to a second embodiment of the present invention. [Diagram 3] (A) Table showing Examples 1 and 2 and Comparative Examples 1 and 2 in which the moldability of the present invention was evaluated when wood flour (with residual lignin) was blended as a cellulosic filler, and (B) Table showing Examples 3 and 4 and Comparative Examples 3 and 4 in which the moldability of the present invention was evaluated when note scraps (with lignin removed) were blended as a cellulosic filler. [Figure 4] 1 is a table showing Examples 5 and 6 and Comparative Example 5 in which the hinge resistance and paintability of molded articles made of resin composite materials were evaluated. [Diagram 5] A standard for evaluating paintability using the cross-cut method. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] (First embodiment) Hereinafter, an embodiment of the present invention will be described with reference to the accompanying drawings. Fig. 1 is a side view showing an example of a production system 10A (10) for carrying out a method for producing a resin composite material according to a first embodiment of the present invention. This production system 10A is composed of a raw material supply device 20A (20) and a kneading device 30 (sealed container).

[0013] The resin composite material according to the first embodiment is manufactured through the following steps. At least one of polysaccharide nanofibers and a hydrophilic cellulose derivative is used as a solute 19, which is dissolved in a solvent 18 to prepare a paste 16. Next, a cellulose-based filler 17 having a powder, fibrous or cotton-like shape and an average width of 20 to 60 μm is prepared. Furthermore, a synthetic resin 15 is also prepared.

[0014] Next, the mixture 12 obtained by mixing at least the paste-like body 16, the cellulose-based filler 17, and the synthetic resin 15 is poured into the inside of the sealed container 30. Then, the mixture 12 is heated and kneaded at a temperature at which the synthetic resin 15 melts to form a molten kneaded body 13. Then, the vent portion 34 of the sealed container 30 is opened to vaporize the solvent 18x ​​and discharge it to the outside, and then the molten kneaded body 13x is taken out.

[0015] The raw material supply apparatus 20A of the first embodiment includes a solvent container 28 for storing a solvent 18, a solute container 29 for storing a solute 19 to be dissolved in the solvent 18, a dissolution tank 26 for dissolving the solute 19 in the solvent 18 to form a paste-like body 16, a filler container 27 for storing a cellulosic filler 17, a first mixing tank 21 for mixing the paste-like body 16 and the cellulosic filler 17 to form a premix body 11, a resin container 25 for storing pellet-shaped synthetic resin 15, and a second mixing tank 22 for mixing the premix body 11 and the synthetic resin 15 to form a mixture body 12.

[0016] Here, the solvent 18 is often an aqueous solvent, but is not limited thereto, and any solvent that dissolves the solute 19 may be appropriately used. The solute 19 may be a polysaccharide nanofiber, a cellulose ether, or a mixture thereof. The cellulose-based filler 17 is a cellulose-based material that exhibits the shape of a powder, a fiber, or a cotton-like body having an average width of 20 to 60 μm.

[0017] The kneading device 30 is composed of an input section 31 for inputting the mixed body 12, a cylinder 33 forming an airtight container in which the input section 31 is provided on the upstream side and a die section 35 from which the molten kneaded body 13 is extruded on the downstream side, a drive section 32 that rotates a screw (not shown) around its axis inside the cylinder 33 to extrude the heated mixed body 12 from upstream to downstream to form the molten kneaded body 13, and a vent section 34 that opens the cylinder 33, which is an airtight container, and discharges moisture contained in the molten kneaded body 13 to the outside.

[0018] The kneading device 30 may be appropriately adopted as long as it is capable of feeding the mixture 12 into a sealed container, kneading it by heating it at a temperature at which the synthetic resin 15 melts, and forming the molten kneaded body 13. For this reason, the kneading device 30 is not limited to a continuous type such as the extruder shown in the figure, and may be a batch type such as a Banbury, kneader, or roller, although not shown.

[0019] The molten kneaded material 13 dehydrated in the vent section 34 is discharged from the most downstream of the cylinder 33. This dehydration is preferably performed so that the moisture content at the thermal flow temperature is 1% or less. In the case of thin-wall inflation molding, the moisture content is further preferably 0.3% or less. In this way, molded products made using a resin composite material whose moisture content is controlled to a certain level or less do not suffer from molding defects due to water foaming.

[0020] For this purpose, the vent section 34 may not only open the inside of the cylinder 33 to the atmosphere and discharge the moisture (solvent 18) contained in the molten kneaded material 13 at a vapor pressure higher than the atmospheric pressure, but also operate a pressure reducing pump to discharge the moisture at a vapor pressure lower than the atmospheric pressure. The discharged molten kneaded material 13x is branched into bundles in the die section 35, cooled and solidified, and then chopped into pellet-shaped resin composite materials.

[0021] Cellulose, a polysaccharide, is a natural polymer in which many β-glucose molecules are polymerized in a linear chain through glycosidic bonds. This linear cellulose molecule is about 0.4 nm wide and 500 nm long. 30 to 40 cellulose molecules are arranged in parallel and overlap each other to form an aggregate, forming a cellulose microfibril (single nanofiber) that is 3 nm wide and 2 to 3 μm long. Furthermore, multiple cellulose microfibrils are bundled together to form a single cellulose fiber that is 20 to 40 μm wide and 1 to 3 mm long.

[0022] This cellulose fiber is the main component of plant cell walls and plant fibers, and is bound to hemicellulose and lignin to form a strong structure. The general methods for extracting cellulose fiber from wood and other materials as a paper raw material (pulp) are classified into chemical processing, which chemically dissolves and removes lignin, and mechanical processing, which mechanically shears the material while keeping the lignin contained.

[0023] The cellulose fibers extracted by mechanical processing are in a state where multiple single fibers are aggregated by the residual lignin, so they are wider and have a smaller aspect ratio than the single fibers themselves, whereas the cellulose fibers extracted by chemical processing, because the lignin has been removed, are separated into individual single fibers and often show a cotton-like structure.

[0024] The cellulose-based filler 17 applied in this embodiment has an average width in the range of 20 to 60 μm. Here, the lower limit of the average width range (20 μm) is determined by the general lower limit of the width of a single fiber of cellulose fiber, and the upper limit of the average width range (60 μm) is determined to maintain the mechanical strength of the molded product at a required level. The cellulose-based filler 17 applied in this embodiment is preferably one extracted by mechanical processing because it has excellent interfacial adhesion with the synthetic resin 15, but one extracted by chemical processing is also no problem.

[0025] As a method for extracting the cellulosic filler 17 by mechanical processing, dry processing is preferred from the viewpoint of production efficiency, and specifically, a high-speed rotary grinder such as a hammer mill or pin mill, or a container-driven mill using a grinding medium (rods, balls, beads, etc.) such as a rotary mill, vibration mill, or planetary mill is preferably used. As a method for converting the cellulosic filler 17 into a fibrous or cotton-like body, a disk refiner, a stone mill, a jet mill, etc., which include a process in which raw materials collide or are ground, are preferably used.

[0026] Also, as raw materials for cellulose-based fillers17, in addition to wood-based materials such as waste paper (newspapers, magazines, cardboard, paper cartons, etc.), paper loss generated during the manufacturing process of paper products, and waste wood, bamboo, rice straw, wheat straw, rice husks, agricultural residues (vegetable waste, tea leaves, tangerine peel, etc.), herbaceous plants, seaweed, etc. Among paper losses, in particular, notebook scraps are considered difficult to recycle as paper, and can be used favorably from the perspective of the SDGs.

[0027] Cellulose fibers that have been mechanically or chemically defibrated to nanoscale widths of 100 nm or less are called cellulose nanofibers (CNFs). Cellulose fibers that have been pulverized and powdered are called cellulose powder. Powders pulverized to a particle size equivalent to the width of cellulose fibers have excellent interfacial adhesion to synthetic resins 15 as cellulose-based fillers 17.

[0028] Mechanical fiber defibration methods for cellulose nanofibers (polysaccharide nanofibers) include the high-pressure homogenizer method, grinder method, underwater counter collision (ACC) method, microfluidizer method, freeze-pulverization method, ultrasonic fiber defibration method, high-speed mixing method, bead mill method, etc. Chemical fiber defibration methods for cellulose nanofibers (polysaccharide nanofibers) include the 2,2,6,6-tetramethylpiperidine 1-oxyl catalyst method (TEMPO oxidation method), enzyme hydrolysis method, carboxymethylation method, phosphoric acid esterification method, etc.

[0029] Cellulose has β-1,4 bonds between D-glucose units, secondary hydroxyl groups at the 2nd and 3rd positions of the glucose basic unit, and a primary hydroxyl group at the 6th position. Cellulose fibers in which hydrogen bonds between these hydroxyl groups are formed within and between cellulose molecules are hydrophilic but do not dissolve in solvents such as water and organic solvents 18. On the other hand, cellulose nanofibers have a much better affinity for water than cellulose fibers, so they dissolve in water and become a paste-like material 16.

[0030] Polysaccharide nanofibers other than cellulose nanofibers also generally have a molecular chain structure similar to that of cellulose nanofibers, and therefore are soluble in solvents. For this reason, polysaccharide nanofibers that form a paste-like body 16 when dissolved in a solvent can be used as the solute 19 of the paste-like body 16, just like cellulose nanofibers. An example of such a polysaccharide nanofiber is chitin nanofiber.

[0031] Furthermore, the cellulose molecule can be made into a more hydrophilic cellulose derivative by introducing a functional group into the hydroxyl group, replacing an atom, etc. A suitable example of such a hydrophilic cellulose derivative is cellulose ether, which is widely used in food and pharmaceutical applications as a thickener, etc. Cellulose ether has a much better affinity for water than cellulose fiber, so it dissolves in water to form a paste-like body 16.

[0032] Examples of such cellulose ethers include methyl cellulose, ethyl cellulose, ethyl methyl cellulose, carboxyl methyl cellulose, carboxyethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, benzyl cellulose, trityl cellulose, cyanoethyl cellulose, aminoethyl cellulose, etc. The hydrophilic cellulose derivative is not limited to such cellulose ethers, and can be used as the solute 19 as long as it forms a paste-like body 16 when dissolved in a solvent.

[0033] As described above, cellulose nanofibers (polysaccharide nanofibers) are highly hydrophilic, and therefore the above-mentioned defibration methods often use water as a dispersion medium. For this reason, a paste-like body 16 in which a polysaccharide nanofiber solute 19 is dissolved in a water solvent 18 may be prepared from the beginning. In this case, the work steps using the dissolution tank 26, solvent container 28, and solute container 29 described above are omitted.

[0034] The synthetic resin 15 is a thermoplastic resin that melts when heated, and can be used without any particular restrictions as long as it has the property of being thermo-fluid when heated and can be generally extruded, such as polyolefin resins such as low-density polyethylene (LDPE), high-density polyethylene (HDPE), and polypropylene (PP), polycarbonate resin (PC), polyethylene terephthalate resin (PET), acrylic-butylene-styrene (ABS), polyvinyl chloride (PVC), polystyrene (PS), and polyamide (PA), which are molded into pellets, as well as biodegradable plastics such as polybutylene adipate-butylene terephthalate copolymer (PBAT) and polylactic acid (PLA), which are decomposed into water and carbon dioxide by the power of microorganisms in the soil. Two or more of these thermoplastic resins may be mixed and used.

[0035] Furthermore, it can be used to recycle waste plastics that have been previously difficult to recycle due to deterioration caused by heat history or ultraviolet rays, etc. In addition, it can be used to recycle waste plastics that contain thermoplastic resins, such as laminated films, composite films, scraps of laminated composite films, and used stretch films that have been discarded without being recycled.

[0036] The blending ratio of the solute 19 in the paste 16 is set to 1 to 30% by weight. If the blending ratio is less than 1% by weight, the viscosity of the paste 16 is too low and the paste 16 is easily separated by gravity from the cellulosic filler 17. On the other hand, if the blending ratio exceeds 30% by weight, the viscosity of the paste 16 is too high and the entire surface of the cellulosic filler 17 cannot be wetted.

[0037] The mixing ratio of the paste-like material 16 in the premix body 11 is set to 10 to 90% by weight. If this mixing ratio is less than 10% by weight, the paste-like material 16 will not be able to wet the entire surface of the cellulosic filler 17, and if it exceeds 90% by weight, the paste-like material 16 will be easily separated from the cellulosic filler 17.

[0038] As described above, if the compounding ratio of the paste-like body 16 and the mixing ratio of the premix body 11 exceed the optimal range, it becomes difficult to form a uniform premix body 11, and the formation of the binder phase at the boundary between the dispersed phase and the continuous phase of the manufactured resin composite material becomes insufficient, resulting in various reduced functions of the molded product.

[0039] The molten kneaded body 13x taken out of the sealed container 30 is cooled and solidified, and then chopped into pellets (resin composite material). After being distributed in the market, the pellet-like resin composite material is remelted in an injection molding machine to be made into various molded products.

[0040] The resin composite material and molded article thus produced are composed of a continuous phase of synthetic resin 15, a dispersed phase of cellulosic filler 17 in the form of powder, fiber or cotton with an average width of 20 to 60 μm, and a binder phase unevenly distributed at the boundary between the continuous phase and the dispersed phase and containing at least one of polysaccharide nanofibers and a hydrophilic cellulose derivative. As a result, the continuous phase and the dispersed phase are strongly bound to each other at the interface, and the molded article exhibits excellent mechanical strength.

[0041] In the molded product of this embodiment, water (solvent 18) is discharged from the molten kneaded body 13 during heating and kneading, so that the solute 19 (polysaccharide nanofiber, hydrophilic cellulose derivative) and the cellulose-based filler 17 are suppressed from coagulating and are finely dispersed in the continuous phase of the synthetic resin 15. This increases the adhesive force at the interface between the continuous phase and the dispersed phase, and increases the melt tension.

[0042] In the raw material supply device 20A of the first embodiment, the premix 11 obtained by mixing the paste 16 and the cellulosic filler 17 is further mixed with the synthetic resin 15 to generate the mixture 12. As a first modification, the premix (not shown) obtained by mixing the paste 16 and the synthetic resin 15 can be further mixed with the cellulosic filler 17 to generate the mixture 12. As a second modification, the paste 16, the cellulosic filler 17, and the synthetic resin 15 can be mixed together to generate the mixture 12 without going through the premix.

[0043] Second embodiment Next, a second embodiment of the present invention will be described with reference to Fig. 2. Fig. 2 is a side view showing an example of a production system 10B (10) for carrying out a method for producing a resin composite material according to the second embodiment of the present invention. This production system 10B is composed of a raw material supplying device 20B (20) and a kneading device 30. In Fig. 2, parts having the same configuration or function as Fig. 1 are indicated by the same reference numerals, and duplicated explanations will be omitted.

[0044] The resin composite material according to the second embodiment is manufactured through the steps described in the first embodiment and the following steps. That is, the mixture 12 is made by mixing at least one of a mixture of a clay mineral substance 45 and a polyhydric alcohol 46 in addition to the paste-like substance 16, the cellulose-based filler 17, and the synthetic resin 15. Note that FIG. 2 shows a form in which the clay mineral substance 45 and the polyhydric alcohol 46 are premixed and then mixed into the mixture 12.

[0045] In addition to the configuration of the first embodiment, the raw material supplying device 20B of the second embodiment further includes a second filler container 47 for containing a clay mineral-based material 45 (in the second embodiment, the cellulose-based filler 17 is contained in the first filler container 27), a dispersant container 48 for containing a polyhydric alcohol 46, and a third mixing tank 23 in which the clay mineral-based material 45 and the polyhydric alcohol 46 are mixed to form a second premix body 42 (in the second embodiment, the mixture of the paste-like body 16 and the cellulose-based filler 17 is referred to as the first premix body 11).

[0046] As the polyhydric alcohol 46, glycols such as ethylene glycol and 1,4 butanediol are preferably used. Two or more kinds of these polyhydric alcohols 46 can be used. As the clay mineral-based substance 45, kaolinite is preferably used. Here, the clay mineral-based substance 45 is a filler for the resin composite material, and the polyhydric alcohol 46 acts as a dispersant that uniformly disperses the filler in the resin composite material. That is, the polyhydric alcohol 46 reduces the viscosity of the synthetic resin 15 that forms the continuous phase when melted, prevents the filler that forms the dispersed phase from coagulating, and contributes to the formation of a fine and uniform dispersed phase in the continuous phase.

[0047] The resin composite material and molded article thus produced are composed of a continuous phase of synthetic resin 15 in which polyhydric alcohol 48 is dissolved, a first dispersed phase of cellulosic filler 17, a second dispersed phase of clay mineral material 45, and a binder phase unevenly distributed at the boundary between the continuous phase and the dispersed phase and containing at least one of polysaccharide nanofibers and a hydrophilic cellulose derivative. As a result, the continuous phase and the dispersed phase are strongly bonded to each other at the interface, and the molded article exhibits excellent mechanical strength.

[0048] This is believed to be due to the fact that the polyhydric alcohol 46, which dissolves in the synthetic resin 15 forming the continuous phase, forms hydrogen bonds with the clay mineral-based substance 45 and cellulose-based filler 17 forming the dispersed phase. In addition, the blending of the polyhydric alcohol 46 and the clay mineral-based substance 45 improves the surface smoothness of the molded product of the resin composite material. Furthermore, mixing liquid paraffin makes it possible to paint the molded product with colored pencils. This is believed to be due to the fact that the liquid paraffin comes to the surface layer of the molded product, increasing its affinity with the wax contained in the colored pencils.

[0049] In the second embodiment of the raw material supplying device 20B, the second premix 42 of the clay mineral material 45 and the polyhydric alcohol 46 is mixed with the paste 16, the cellulosic filler 17, and the synthetic resin 15 to generate the mixture 12. As a first modification, the clay mineral material 45 and the polyhydric alcohol 46 can be separately added to generate the mixture 12 without going through the second premix 42. As a second modification, only either the cellulosic filler 17 or the synthetic resin 15 can be added to generate the mixture 12. EXAMPLES

[0050] Next, examples that confirmed the effect of this embodiment will be described. Fig. 3(A) is a table showing Examples 1 and 2 and Comparative Examples 1 and 2 in which the moldability of the present invention was evaluated when wood flour (with residual lignin) was blended as the cellulosic filler 17. Fig. 3(B) is a table showing Examples 3 and 4 and Comparative Examples 3 and 4 in which the moldability of the present invention was evaluated when note scraps (without lignin) were blended as the cellulosic filler 17.

[0051] The wood flour used as the cellulose-based filler 17 in Figure 3(A) is made by powdering construction waste. Wood flour is used because construction waste still contains lignin and has been treated with preservatives, making it difficult to defibrate and turn it into a fibrous form. Note scraps used as the cellulose-based filler 17 in Figure 3(B) are made into a fibrous / cotton-like material by defibration processing. The reason they are made into a fibrous / cotton-like material is that the lignin is removed from the note scraps during the papermaking process, making them relatively easy to defibrate.

[0052] The evaluation of the molded products was carried out on the formability by the inflation method of an 80μm-thick film used for heavy-duty bags, and on the formability by the T-die method of a 500μm-thick sheet generally used for vacuum and pressure molding. The evaluation of the inflation method and the T-die method was carried out by classifying the condition of each molded film and sheet into the following categories: smooth ◎, no holes ○, holes △, and unacceptable ×. It is generally said that film and sheet processing of resin composite materials containing cellulose-based fillers17 is highly difficult.

[0053] Example 1 In Example 1, the cellulose-based filler 17 was wood flour obtained by crushing construction waste wood to an average width of 60 μm using a vibration ball mill. The paste-like body 16 was made by mixing and stirring carboxymethyl cellulose (hereinafter referred to as "CMC") as the solute 19 at a mass ratio of 1 and water as the solvent 18 at a mass ratio of 20. The synthetic resin 15 was low-density polyethylene (hereinafter referred to as "LDPE"). The composition of Example 1 was 40 parts by weight of the synthetic resin 15 (LDPE), 30 parts by weight of the cellulose-based filler 17 (wood flour), and 30 parts by weight of the paste-like body 16.

[0054] Using the composition of Example 1, a film was formed by the inflation method at a take-off speed set by conversion so that the thickness would be 80 μm. As a result, a film without holes could be formed. However, when the unevenness of the film surface was measured at 10 points with a micrometer to evaluate the unevenness of the thickness, the measured values ​​varied and it could not be said that the film was smooth.

[0055] The composition of Example 1 was used to form a sheet using the T-die method at a take-off speed set by conversion so that the thickness would be 500 μm. As a result, a sheet without holes could be formed. Then, the unevenness of the sheet surface was measured at 10 points using a micrometer to evaluate the thickness unevenness, and the values ​​were almost the same, indicating a smooth state.

[0056] Comparative Example 1 Comparative Example 1 differs from Example 1 in that the cellulose-based filler 17 (wood flour) was pulverized to an average width of 300 μm using a pin mill grinder; otherwise, the paste-like material 16 and synthetic resin 15 and their compositions were the same.

[0057] When the composition of Comparative Example 1 was used to form a film by inflation, many holes occurred and the film could not be formed. A sheet was formed by the T-die method at a take-up speed set by conversion so that the thickness would be 500 μm. Although it was possible to form a sheet, holes sometimes occurred in the areas where the grain size of the wood powder was large.

[0058] Example 2 In Example 2, kaolinite was further added as the clay mineral-based material 45 and ethylene glycol (hereinafter referred to as "EG") as the polyhydric alcohol 46 to Example 1. The composition of Example 2 was 40 parts by weight of synthetic resin 15 (LDPE), 25 parts by weight of cellulosic filler 17 (wood flour), 25 parts by weight of paste-like body 16, 5 parts by weight of polyhydric alcohol 46 (EG), and 5 parts by weight of clay mineral-based material 45 (kaolinite).

[0059] The composition of Example 2 was used to form a film by the inflation method at a take-off speed set based on conversion so that the thickness would be 80 μm. As a result, a smooth film could be formed. A sheet was also formed by the T-die method to a thickness of 500 μm, and was also formed in a smooth state.

[0060] Comparative Example 2 Comparative Example 2 differs from Comparative Example 1 in that a solvent 18 (water) was used alone instead of the paste-like body 16, while the filler 17 (wood flour) and synthetic resin 15 (LDPE) and their blending were the same. In Comparative Example 2, the inflation method was not possible at all to blow up the mixture, making it impossible to form a film, and the T-die method also made it impossible to form a sheet, as the mixture became mesh-like and broke.

[0061] From the results of Example 1, Example 2, and Comparative Example 1 described above, it is considered that the CMC contained in the paste-like body 16 acts as a bridge between the wood flour filler 17 and the synthetic resin 15, and that the two are integrated and thermally flow without being separated. On the other hand, if the width of the wood flour filler 17 becomes larger than the thickness of the film or sheet, the two are easily separated, making it difficult for them to be integrated and thermally flow.

[0062] Example 3 Example 3 differs from Example 1 in that the cellulosic filler 17 is made of scraps of notebook paper milled into a cotton-like material by a jet mill. Other than the cellulosic filler 17, the paste-like material 16 and the synthetic resin 15, and the composition thereof, are the same as those of Example 1 and Example 3.

[0063] Using the composition of Example 3, a film was formed by the inflation method at a take-off speed set by conversion so that the thickness would be 80 μm. As a result, a film of the same state level as in Example 1 could be formed. In addition, a sheet formed by the T-die method to a thickness of 500 μm was also formed in the same smooth state as in Example 1.

[0064] Comparative Example 3 Comparative Example 3 differs from Example 3 in that the cellulose-based filler 17 (notebook scraps) was pulverized to an average width of 300 μm using a pin mill crusher; otherwise, the paste-like material 16 and synthetic resin 15 and their compositions were the same.

[0065] When the composition of Comparative Example 3 was used to form a film using the inflation method, many holes occurred and the film could not be formed. On the other hand, when the composition was used to form a sheet with a thickness of 500 μm using the T-die method, the sheet could be formed without any holes. This is thought to be because the filler 17 made from notebook scraps that does not contain lignin is more easily atomized during kneading than the filler 17 made from wood flour that contains lignin.

[0066] Example 4 Example 4 differs from Example 2 in that the cellulosic filler 17 is made of note scraps pulverized into a flocculent material by a jet mill. Other than the filler 17 (note scraps pulverized into a flocculent material), the paste-like material 16 and synthetic resin 15 and their blends are the same as those in Example 1. With the blend of Example 4, a smooth film could be formed by the inflation method, and a smooth sheet could also be formed by the T-die method.

[0067] Comparative Example 4 Comparative Example 4 differs from Comparative Example 3 in that a solvent 18 (water) was used alone instead of the paste-like body 16, while the filler 17 (wood powder) and synthetic resin 15 and their blending ratios were the same. In Comparative Example 4, similar to Comparative Example 2, the inflation method was unable to blow the mixture up at all, making it impossible to form a film, and the T-die method also made the mixture break as it became mesh-like, making it impossible to form a sheet.

[0068] Comparing Example 1 and Example 3, and Example 2 and Example 4, in both cases, the thickness of the obtained film and sheet was measured to be smaller when notebook scraps were used as the filler 17. This is thought to be because the filler 17 with a larger aspect ratio has higher adhesion to the synthetic resin 15 even if the width is the same.

[0069] FIG. 4 is a table showing Examples 5 and 6 and Comparative Example 5 in which the hinge resistance and paintability of molded products of resin composite materials were evaluated. FIG. 5 shows the evaluation criteria for paintability in the cross-cut method. Here, the hinge resistance is expressed as the number of times a molded product made by injection molding a resin composite material in a mold for plastic models can be repeatedly folded before it breaks. As the evaluation criteria, a number of times that exceeds 50 times is indicated as ◯, and a number that does not exceed 50 times is indicated as the number of times. The paintability was evaluated according to the cross-cut method (JIS K5600-5-6), and the results were expressed as a classification of 0 to 5. In this classification, the smaller the number, the better the paintability.

[0070] The resin composite material of Example 5 was prepared by mixing the synthetic resin 15 as polystyrene (hereinafter referred to as "PS"), the cellulose-based filler 17 as cellulose powder (hereinafter referred to as "CP") having an average width of approximately 30 μm, the polyhydric alcohol 46 as ethylene glycol (hereinafter referred to as "EG"), and the clay mineral substance 45 as kaolinite in the weight parts shown in the table.

[0071] The resin composite material of Example 6 was prepared by further mixing polyhydric alcohol 46 as 1,4 butanediol (hereinafter referred to as "BDO") and liquid paraffin in the amounts shown in the table in comparison with the mixture of Example 5. The resin composite material of Comparative Example 5 was prepared by mixing synthetic resin 15 with 100 parts by weight of polystyrene.

[0072] Example 5 just missed the evaluation criteria for hinge resistance, but was rated higher in paintability, at category 2, than Comparative Example 5. In contrast, Example 6 not only met the evaluation criteria for hinge resistance, but also received a high rating of category 0 for paintability. In addition, Examples 5 and 6 were able to be painted with colored pencils, which was not possible with Comparative Example 5. [Explanation of symbols]

[0073] 10 (10A, 10B)... manufacturing system, 11... premix body (first premix body), 12... mixture, 13, 13x... molten kneaded body, 15... synthetic resin, 16... paste, 17... cellulose-based filler, 18, 18x... solvent (aqueous solvent), 19... solute, 20A, 20B... raw material supply device, 21... first mixing tank, 22... second mixing tank, 23... third mixing tank, 25... resin container, 26... dissolution tank, 27... filler container (first filler container), 28... solvent container, 29... solute container, 30... kneading device (sealed container), 31... input section, 32... drive section, 33... cylinder, 34... vent section, 35... die section, 42... second premix body, 45... clay mineral-based substance, 46... polyhydric alcohol, 47... second filler container, 48... dispersant container.

Claims

1. A step of preparing a paste-like body in which at least one of polysaccharide nanofibers and a hydrophilic cellulose derivative is dissolved as a solute in a solvent; preparing a cellulose-based filler having a powder, fibrous or cotton-like shape and an average width of 20 to 60 μm; A step of pouring a mixture of at least the paste-like body, the cellulose-based filler, and a synthetic resin into a sealed container; a step of heating and kneading the mixture at a temperature at which the synthetic resin melts to form a molten kneaded body; and opening the sealed container to discharge the vaporized solvent to the outside, and then removing the molten kneaded body.

2. 2. The method for producing a resin composite material according to claim 1, wherein the mixture is A step of mixing the paste-like body and the cellulose-based filler to obtain a premix body; and mixing the premix with the synthetic resin.

3. The method for producing a resin composite material according to claim 2, The blending ratio of the solute in the paste is 1 to 30% by weight, A method for producing a resin composite material, wherein the mixing ratio of the paste-like body in the premix is ​​10 to 90% by weight.

4. The method for producing a resin composite material according to claim 1 or 2, A method for producing a resin composite material, wherein the polysaccharide nanofiber is a cellulose nanofiber, the hydrophilic cellulose derivative is a cellulose ether, the solvent is water, the cellulose-based filler is a notebook scrap, and the synthetic resin is a used stretch film.

5. The method for producing a resin composite material according to claim 1 or 2, The method for producing a resin composite material further comprises a step of mixing the mixture with at least one of a clay mineral-based material and a polyhydric alcohol.

6. The method for producing a resin composite material according to claim 5, A method for producing a resin composite material in which a clay mineral-based substance and a polyhydric alcohol are premixed.

7. A method for producing a molded product using the method for producing a resin composite material according to claim 5, the synthetic resin contains polystyrene, the clay mineral-based material contains kaolinite, the polyhydric alcohol contains at least one of ethylene glycol and 1,4-butanediol, and the mixture is further mixed with liquid paraffin; The resin composite material thus produced is molded by a T-die method, an injection molding method or a profile extrusion method, and the molded product is colored with colored pencils.

8. A continuous phase of a synthetic resin; A dispersed phase of a cellulose-based filler having a powder, fibrous or cotton-like shape with an average width of 20 to 60 μm; a binder phase which is unevenly distributed at the boundary between the continuous phase and the dispersed phase and which contains at least one of a polysaccharide nanofiber and a hydrophilic cellulose derivative.

9. The resin composite material according to claim 8, A resin composite further comprising a dispersed phase of a clay mineral-based material.

10. The resin composite material according to claim 8 or 9, The resin composite material comprises a dispersed phase and a binder phase, the total of which accounts for 50% by weight or more.

11. A molded product obtained by molding the resin composite material according to claim 8 or 9 into a sheet or film having a thickness of 0.2 mm or less.

Citation Information

Patent Citations

  • Manufacturing method of resin composite material, resin composite material and molded product

    JP7061239B1